2017
DOI: 10.1590/0103-8478cr20151147
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of resistance to Meloidogyne incognita in melon

Abstract: In order to assess the genetic control of resistance in the melon ‘Gaúcho Redondo’ to the root-knot nematode Meloidogyne incognita, an experiment was conducted in a randomized complete block design with three blocks and six treatments using the parental lines ‘Gaúcho Redondo’ (P1 resistant) and JAB 20 (P2 susceptible), as well as F1, F2, and backcross generations (RC1P1 and RC1P2). Seventy days after inoculation, individual plants were evaluated for resistance using the nematode reproduction factor (RF). The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…The inheritance of quantitative characters is complex, and many genes has a minor contribution to the phenotype. Inheritance of quantitative characters is generally studied by estimating population parameters (Rosmaina et al 2016;Candido et al 2017;Rohaeni and Yunani 2017;Coelho et al 2019).…”
Section: Principal Component Analysis (Pca) Of Quantitative Charactermentioning
confidence: 99%
“…The inheritance of quantitative characters is complex, and many genes has a minor contribution to the phenotype. Inheritance of quantitative characters is generally studied by estimating population parameters (Rosmaina et al 2016;Candido et al 2017;Rohaeni and Yunani 2017;Coelho et al 2019).…”
Section: Principal Component Analysis (Pca) Of Quantitative Charactermentioning
confidence: 99%
“…Quantitative traits have complex inheritance, conditioned by many genes with small individual effects, and are greatly affected by the environment. In these cases, the inheritance and variation of traits are studied on the population level through estimation of genetic parameters (Candido et al 2017, Rohaeni and Yunani 2017, Sakulphrom et al 2017, Coelho et al 2019. Cabral et al (1997) reported that segregations for leaf types was in accordance with the frequencies expected from the Collins and Kerns (1946) 2-gene model, with the Primavera cv.…”
Section: Genotypic Hypothesismentioning
confidence: 99%